Analysis of Physical Concepts in Nganjuk Tourism Banyu Biru Hot Springs - Galuh Dwi Krisanti; Siti Nur Aisah; Adrian Bagas Damarsha; Nadi Suprapto; Setyo Admoko; Kifle Kassaw Mulatu (Prodi S2 Pendidikan Fisika Universitas Negeri Surabaya, 2026)
Banyu Biru hot springs is one of the tourist attractions in Gondangwetan Village, Jatikalen District, Nganjuk Regency, which has geothermal manifestations in the form of hot springs, which indicate the existence of a geothermal reservoir below the surface. This study aims to analyze the physics concepts found in Banyu Biru hot spring tourism, as well as the physics that shapes it. This study uses qualitative research in the form of a literature review. The research was conducted by collecting library sources, classifying data, managing data, citing references, abstracting data, interpreting data, and drawing conclusions. Based on the results and discussion, it can be concluded that the Banyu Biru hot springs are a local culture in the Nganjuk Regency area. The formation of the Banyu Biru hot springs was influenced by the location of Nganjuk Regency which is between Mount Wilis and Mount Pandan. Based on the location of Nganjuk Regency, it is possible that it has something to do with the volcanic activity of the volcano. The geothermal phenomenon at the Banyu Biru hot springs was discovered after drilling a well to irrigate the rice fields. The hot water has a temperature of approximately 37°C with a depth of 250-300 meters. Apart from that, the Banyu Biru hot springs in Nganjuk Regency can be studied physically, namely there are concepts regarding geothermal energy, geothermal energy, geothermal systems, conduction and convection. This study can raise public awareness of local cultural identity through the integration of local wisdom into physics education.